The Concepts of Predestination and Free Will in Mu‘tazilite Thought (A Methodological Study from Theological to Philosophical Issues - Mahmood Hameed, Najlaa ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
The study of this issue in Mu‘tazilite thought is considered one of the most significant topics, not only within Islamic intellectual discourse but also within human thought in general, as it touches on both Islamic creed and human nature. Numerous authors and researchers have documented the Mu‘tazilites’ rich intellectual contributions, which have greatly enriched the understanding of Islamic heritage, particularly concerning this issue, offering insights beneficial to the Islamic world and to those of diverse religions and cultures who engaged with them. The concept of free will attracted critical observations and intellectual debates, shaping a dynamic intellectual movement characterized by innovation and the integration of religious belief with virtue, ethics, and philosophical thought. Despite differing scholarly positions—ranging from denying Greek influence to explicitly acknowledging it—the methodological approach to presenting the issue, with a focus on its specific and general dimensions, has led to a deeper and more meaningful exploration of the intersection between philosophy and religion. DOI: https://doi.org/10.54633/2333-024-056-016